Organization of work with undesired events within the system of medical activities quality and safety internal control with the use of digital technology - E. V. Kolyado; V. A. Peleganchuk; T. E. Shults; A. N. Povalikhin; V. V. Lazareva (Acta Biomedica Scientifica, 2023)
In accordance with the current legislation a healthcare organization shall be obliged to provide conditions for safe delivery of healthcare to patients and medical personnel performance.Implementation of effective model of medical activities quality and safety internal control producing meaningful result is a current license requirement to a healthcare organization.Implementation of risk-oriented approach to medical activities quality and safety management is an important constituent of modern stage of the Russian Federation healthcare functioning.It is necessary to understand sources of potential hazard within an organization, consider and analyze all undesired events and incidents arising in the process of a healthcare organization functioning and their reasons, take preventive measures to avoid them.The tasks of digital transformation in the Russian Federation healthcare are development of integrated digital contour, transition to electronic document flow, reduction of medical personnel’s time expenditure not involving delivery of healthcare.Implementation of customer centricity and digitalization principles is an absolute trend of modern stage of development of the Russian Federation healthcare. It determines necessity of development of present-day accounting and analyzing data system on undesired events in a healthcare organization.The article presents the experiment of Federal Center for Traumatology, Orthopedics and Endoprosthetics (Barnaul, Russian Federation) in establishing system of work with undesired events and managerial decision-making on their avoidance and prevention with the use of present-day digital technology resulting in credible frequency reduction of undesired events in the space of 2.5 years.